The effects of insecticides on two splice variants of the glutamate‐gated chloride channel receptor of the major malaria vector, Anopheles gambiae - Atif, Mohammed (John Wiley and Sons Inc., 2019)

(untitled) (Br J Pharmacol)
BACKGROUND AND PURPOSE: Between half to 1 million people die annually from malaria. Anopheles gambiae mosquitoes are major malaria vectors. Unfortunately, resistance has emerged to the agents currently used to control A. gambiae, creating a demand for novel control measures. The pentameric glutamate‐gated chloride channel (GluCl) expressed in the muscle and nerve cells of these organisms are a potentially important biological target for malaria control. The pharmacological properties of Anophiline GluCl receptors are, however, largely unknown. Accordingly, we compared the efficacy of four insecticides (lindane, fipronil, picrotoxin, and ivermectin) on two A. gambiae GluCl receptor splice variants with the aim of providing a molecular basis for designing novel anti‐malaria treatments. EXPERIMENTAL APPROACH: The A. gambiae GluCl receptor b1 and c splice variants were expressed homomerically in Xenopus laevis oocytes and studied with electrophysiological techniques, using two‐electrode voltage‐clamp. KEY RESULTS: The b1 and c GluCl receptors were activated with similar potencies by glutamate and ivermectin. Fipronil was more potent than picrotoxin and lindane at inhibiting glutamate‐ and ivermectin‐gated currents. Importantly, b1 GluCl receptors exhibited reduced sensitivity to picrotoxin and lindane. They also recovered from these effects to a greater extent than c GluCl receptors CONCLUSIONS AND IMPLICATIONS: The two splice variant subunits exhibited differential sensitivities to multiple, structurally divergent insecticides, without accompanying changes in the sensitivity to the endogenous neurotransmitter, glutamate, implying that drug resistance may be caused by alterations in relative subunit expression levels, without affecting physiological function. Our results strongly suggest that it should be feasible to develop novel subunit‐specific pharmacological agents.